Prevalence Mapping of Schistosoma mansoni Among Pre-school Age Children in Rwanda - Rujeni, Nadine; Bayingana, Jean Bosco; Nyandwi, Elias; Ntakarutimana, Amans; Kagabo, Joseph; Rutayisire, Reverien; Shema, Eliah; Kanimba, Philbert; Mbonigaba, Jean Bosco; Ruberanziza, Eugene (Frontiers in Pediatrics, 2022)
Schistosomiasis is endemic in Rwanda and control programs have been implemented with a special focus on school-aged children (SAC) ignoring pre-school aged children (pre-SAC) for which the actual prevalence of the disease is not well established. This study consisted of a cross-sectional quantitative mapping of the distribution of schistosomiasis and identification of associated risk factors among pre-SAC throughout the country. The study covered all the 17 Districts of Rwanda endemic for schistosomiasis with a total sample of 4675 children enrolled from 80 purposively selected villages. The Parasitological assessment of children’s urine and stool samples was conducted using CCA and Kato Katz methods respectively for infection detection. A standard questionnaire was used to collect data on the risk factors and geospatial assessment was performed using tablets and GPS to record geographic coordinates for plotting locations on maps using ArcGIS software. The overall prevalence of S mansoni infection across the surveyed areas was 24% and 0.8 by CCA and Kato-Katz, respectively. Infection was significantly associated with bathing children in open water bodies. Furthermore, pre-SAC looked after by siblings (sisters) were twice as much likely to be infected compared to those looked after by mothers. Schistosomiasis control interventions are needed for pre-SAC to limit their exposure to open water bodies with expectations of adapted chemotherapy to be availed. Community based deworming campaigns may be the best way to ensure good treatment coverage of pre-SAC in Rwanda.